Perencanaan Website Menggunakan Aplikasi Blogger Pada UMKM Toko Daffo Boneka - Gina Vionalita; Noni Anggraini; Nashwa Harvila Maharani (CV. ITTC INDONESIA, 2024)
sales system at the Daffo Doll Shop has so far been carried out in collaboration with doll shops which take a long time to market the dolls so they are considered less effective and efficient. The slow development of sales is due to the lack of promotion of Daffo Doll to the public so that not all levels of society know about this company. Therefore, we need a web-based or internet plan that can help in marketing dolls so that sales transactions can be carried out quickly anywhere and at any time by all levels of society. The aim of planning a website using this blogger is to provide information about the dolls being marketed in detail to potential buyers, making it easier for potential buyers to get the information they need and to introduce the Daffo Doll Shop to all levels of society so that they can expand their marketing reach with the aim of increasing sales.